Clinical value of quantitative echocardiographic features in preterm infants with necrotizing enterocolitis - Wenmei li; Wenqiang Sun; Zexi Sun; Huawei Wang; Xueping Zhu (Scientific Reports)
Abstract This study investigated the correlation between quantitative echocardiographic characteristics within 3 days of birth and necrotizing enterocolitis (NEC) and its severity in preterm infants. A retrospective study was conducted on 168 preterm infants with a gestational age of < 34 weeks. Patients were categorized into NEC and non-NEC groups. Clinical and quantitative cardiac ultrasound characteristics were compared using univariate and multivariate analyses. Additionally, the NEC group was divided into two subgroups according to Bell’s staging, and the quantitative echocardiographic characteristics were compared. Overall, 141 preterm infants were included. Percentage of antenatal glucocorticosteroid administrations was lower in the NEC group than those in the control group. Umbilical vein cannulation, antibiotic duration, total red blood cell infusion, duration of total parenteral and total enteral nutrition, respiratory failure, hemodynamically significant patent ductus arteriosus, anemia, neutropenia, hyperbilirubinemia were significantly higher than those in the control group. The maximum shunt velocity and differential pressure (P) on the pulmonary side of the arterial conduit were significantly lower, whereas the left ventricular ejection fraction (LVEF) and left ventricular fractional shortening (LVFS) were significantly higher in the NEC group. Antenatal glucocorticoid use and umbilical vein cannulation were protective factors against NEC. Anemia, hyperbilirubinemia, and lower P were risk factors for NEC. P was significantly lower and LVFS and LVES were significantly higher in preterm infants in the NEC II B-III group than those in the NEC II A group. Preterm infants with NEC have significant abnormalities in some quantitative features on echocardiography within 3 days after birth, and a lower P may be a risk factor for the development of NEC.